Comprehensive analysis of common safety profiles and their predictive factors in 520 records of liver cancer patients treated by drug-eluting beads transarterial chemoembolization. Issue 26 (June 2018) - Sun, Junhui; Zhou, Guanhui; Zhang, Yuelin; Zhou, Tanyang; Nie, Chunhui; Zhu, Tongyin; Chen, Shengqun; Wang, Baoquan; Yu, Ziniu; Wang, Hongliang; Chen, Xinhua; Hong, Liangjie; et al.
Abstract : Abstract: This study aimed to investigate the difference of common adverse events (AEs) between patients experienced first drug-eluting beads transarterial chemoembolization (DEB-TACE; FD) and second or higher DEB-TACE (SHD), and the factors influencing AEs. Five hundred twenty DEB-TACE records were retrospectively reviewed in this cohort study, among which 284 and 236 records were in FD and SHD groups, respectively. The incidence and/or severity of pain, fever, vomiting, and increased blood pressure (BP) were collected. Pain numerical rating scale (NRS) score, pain severity, body temperature, fever severity, and fever lasting days were higher in FD group than in SHD group, while no difference of vomiting and increased BP between 2 groups were disclosed. Age ≥65 years was associated with decreased high fever and less possibility of vomiting in FD group, and lower pain and fever severity in SHD group; Male decreased the possibility of vomiting in both the groups, and reduced increased BP incidence in SHD group; diabetes history correlated with decreased pain degree and less fever in FD group. In conclusion, SHD was better tolerated compared with FD in liver cancer patients, and older age as well as male were correlated with less occurrence or severity of common AEs in DEB-TACE operation.